Kajian Partisipasi Masyarakat Dalam Pariwisata Berkelanjutan Di Simanindo, Kabupaten Samosir - Sihotang, Harlen; Ritonga, Isniar TL (Outline Publisher, 2025)
Simanindo is a sub-district of Samosir district, situated on the shores of Lake Toba. It is an emerging tourism destination. Community engagement may bolster various facets of sustainable tourism to foster its growth. Sustainable tourism is a type of tourism that enhances both the environmental and socio-cultural components. The involvement of the community is crucial for the growth of Simanindo's tourist industry, since it plays a vital role in the establishment of sustainable tourism in the area. The aim of this research is to find out what participation the community has in developing sustainable tourism in Simanindo. The data collection method involves distributing 100 questionnaires to local communities in four tourist attraction locations in Simanindo. Each tourist attraction will receive 25 questionnaires. Additionally, interviews will be conducted with eight resource persons who have resided in the research location for over five years. Each tourist attraction will have two resource persons whose work is connected to tourism. Community participation in sustainable tourism has three main components: contributing to the provision of goods or services, participating in the development of infrastructure and facilities, and engaging in the design of Pokdarwis (Tourism Awareness Groups). These forms of participation are closely connected to both environmental and socio-cultural aspects of sustainable tourism. These results summarize the local community's opinion regarding community participation in the development of sustainable tourism in Simanindo. The results of this research conclude that the most dominant form of community participation is the provision of goods and services and the most dominant aspect in sustainable tourism is the socio-cultural aspect in Simanindo sub-district, Samosir district.